How Major Central Banks Reacted to the Inflationary Wave of the Early 2020s : The Case of the ECB - Durkó, Ruben (Financial and economic review, 2023)
From 2021 onwards, inflationary pressures around the world have forced most central banks to raise interest rates from a level that had long been around 0 per cent. However, some central banks, including the European Central Bank (ECB), have often been the subject of criticism for not paying enough attention to the emerging inflationary spiral. The author examines whether there is evidence that the ECB started to tighten monetary conditions later than it had done in the past. The interest rate rule widely applied by the academic community and the results of the pseudo-forecast based on this rule show that the ECB moved later than its historical behaviour would suggest, i.e. it started tightening three quarters later than indicated in the model; nevertheless, by the end of 2022, the actual and the theoretical rates were in line thanks to the intensive rate hikes.